Актуальні проблеми кримінально-правової протидії тероризму в Україні - Юртаєва, К. В.; Yurtayeva, K. V.; ORCID: http://orcid.org/0000-0002-6096-2020; ResearcherID: D-1818-2016 (Вісник Кримінологічної асоціації України. - 2015. - № 1 (9). - С. 200-211., 2015)
У статті розглянуто проблемні питання кваліфікації тероризму, відмежування тероризму від деяких злочинів проти основ національної безпеки (диверсії та зло чинів, пов’язаних із сепаратизмом). Проаналізовано особливості застосування процедури екстрадиції щодо вказаних злочинів. Розглянуто характеристики тероризму як злочину міжнародного характеру. Визначено відмінності терористичних актів від воєнних злочинів. Окрему увагу приділено особливостям кваліфікації актів тероризму в умовах міжнародних та неміжнародних збройних конфліктів.

A lot of attention was paid to the issues of terrorism counteraction in Ukraine during recent decades, namely in the papers of the following scholars: V.F. Antipenko, V.O. Hlushkov, V.M. Dromin, V.P. Yemelianov, V.P. Zhuravlov, N.A. Zelinska, V.V. Kovalenko, O.M. Kostenko, S.Ya. Lykhova, M.I. Khavroniuk, S.S. Yatsenko and others. However, in the conditions of armed conflict on the territory of Ukraine, the issue of qualifying terrorism manifestations in the regions of armed conflict has gained particular importance. The objective of the article is to highlight the issues of terrorism qualification, its dissociation from separatism manifestations and from other crimes against the basis of the national security of Ukraine; analysis of peculiarities of implementing the procedure of extradition concerning these crimes. Based on the conducted comparative analysis the author makes a conclusion that terrorism and crimes under the Articles 109, 110 and 113 of the Criminal Code of Ukraine have in a number of cases certain common features. Thorough study of their corpus delicti allows to determine their distinctive features that lie in the sphere of the objective components, modus operandi and motivational sphere. At the same time, the genetic similarity of these crimes, existence of such common features as violent modus operandi, focus on doing harm to an unspecified number of people, political motivation, can cause some difficulties during their qualification by investigative and court agencies of Ukraine. Special attention is focused on the fact that the problem of terrorism counteraction has long gone beyond just local problem of some countries. Characteristics of terrorism as an international crime are considered; international and legal base of terrorism counteraction is defined. It is determined that although such crimes as terrorism, encroachment on territorial integrity and inviolability of Ukraine and sabotage are the same according their severity, have considerable similarity by the features of objective and subjective sides, extradition procedure is different for these crimes. Terrorism can not be considered as political offence, and the country, where the alleged offender is, can not refuse his extradition, referring on political views and beliefs of the person whose extradition is requested. The opposite situation occurs with the crimes against the national security of Ukraine. Notification about extradition failure of a person for political reasons, except for murder or attempted murder of the president or a member of his family may be used to the latter. The difference of terrorist acts from war crimes is analyzed. It is determined that war crimes from the objective side may have some similarities to terrorism, but they are directly related to the armed conflict and have a much higher degree of public danger. It is emphasized that the existence of an armed conflict does not preclude the use of norms concerning the struggle against terrorism. It is determined that some acts of terrorism should be distinguished from war crimes, which are committed during armed conflicts of an international and non-international character. However, if the terrorist attacks have mass and systematic nature, and in the case of these crimes’ large-scale commission, they can be qualified as war crimes, even in situations of armed conflict of noninternational character.

В статье рассмотрены проблемные вопросы квалификации терроризма, отграничение терроризма от некоторых преступлений против основ национальной безопасности Украины. Проанализированы особенности применения процедуры экстрадиции в отношении указанных преступлений. Выделены отличия террористических актов от военных преступлений. Отдельное внимание уделено особенностям квалификации актов терроризма в условиях международных и немеждународных вооруженных конфликтов.
Юртаєва, К. В. Актуальні проблеми кримінально-правової протидії тероризму в Україні // Вісник Кримінологічної асоціації України. - 2015. - № 1 (9). - С. 200-211.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; терористичний акт; кваліфікація злочину; злочини проти основ національної безпеки; сепаратизм; міжнародний тероризм; екстрадиція; воєнні злочини; act of terrorism; qualification; crimes against the basis of the national security; separatism; international terrorism; extradition; war crimes; террористический акт; терроризм; тероризм; квалификация преступления; преступления против основ национальной безопасности; сепаратизм; международный терроризм; экстрадиция; военные преступления